Implementation of agile in developing prescription drug management system to enhance user experience in pharmacies - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
This study addresses the development of a pharmacy prescription management system in response to the challenges faced by traditional pharmacy practices. Employing Agile methodology, the research focuses on systematically analyzing user needs, implementing iterative development processes, and evaluating system functionality and user acceptance. Through interviews, observations, and surveys, user requirements are identified and prioritized, guiding the development of the system's features. The Agile approach allows for flexibility and responsiveness to evolving user needs, ensuring that the developed system aligns with user expectations. Results indicate that the system successfully meets user requirements and garners positive acceptance, highlighting the effectiveness of Agile practices in software development for the pharmaceutical industry. The study contributes to the understanding of Agile methodologies' applicability in addressing real-world challenges, ultimately enhancing efficiency and user satisfaction in pharmacy operations